Magnetic targeting of stem cell therapies - Harrison, Richard P. (2016)
Stem cells may offer solutions for many health issues facing the world’s population. Early Biotech-led approaches are supporting novel mesenchymal stem cell (MSC) therapies through biomedical trials. However, their potential benefits are currently curtailed by challenges linked to high cell dose requirements which pose availability and manufacturing challenges, combined to suboptimal delivery methodologies. Whilst systemic delivery may be suitable for many pharmaceuticals, more complex and selective treatments such as emerging cell therapies require smarter targeting strategies on safety and cost/benefit grounds.